Closed-loop solvometallurgical process for recovery of lead from iron-rich secondary lead smelter residues. Issue 79 (26th October 2017) - Forte, Federica; Horckmans, Liesbeth; Broos, Kris; Kim, Eunyoung; Kukurugya, Frantisek; Binnemans, Koen
Abstract : A solvometallurgical process based on acetic acid was developed for the recovery of lead from iron-rich residues (matte and slag). Abstract : A solvometallurgical process based on the use of concentrated acetic acid as lixiviant is proposed as an alternative for conventional hydrometallurgical processes to recover lead from iron-rich industrial residues generated by recycling of spent lead-acid batteries in a secondary lead smelter. Under the optimal conditions, a high selectivity for lead was obtained: more than 90% of the lead content could be dissolved, while only a small amount of iron (<6%) was codissolved. Lead was quantitatively recovered from the acetic acid leachate by addition of a stoichiometric amount of sulphuric acid. Acetic acid was recycled by distillation and reused in the leaching step, so that a closed-loop process was obtained. The process was optimised for iron-rich residue (matte), but also a proof-of-principle is given for lead recovery from another lead-containing residue (slag). The main advantages of this solvometallurgical process are the low power consumption (room-temperature process), the low consumption of chemicals (only sulphuric acid is consumed), full recycling of the acetic acid and the limitation of waste water formation.